Add-on atypical anti-psychotic treatment alleviates auditory verbal hallucinations in patients with chronic post-traumatic stress disorder. (14th May 2019) - Cheng, Langlang; Zhu, Jingjing; Ji, Feng; Lin, Xiaodong; Zheng, Lidan; Chen, Ce; Chen, Guangdong; Xie, Zuoliang; Xu, ZhangJi; Zhou, Chunhua; Xu, Yong; Zhuo, Chuanjun
Highlights: Auditory verbal hallucinations (AVHs) are severe symptoms of post traumatic distress disorder (PTSD). AVHs is related to brain functional disturbances in the salience network(SN). PTSD patients with AVHs benefit from atypical anti-psychotic treatment. Atypical anti-psychotic treatment can decrease the functional activity of SN. The decrease in functional connectivity within the SN was significantly correlated with the reduction in total AVHs assess scores. Abstract: Auditory verbal hallucinations are common symptoms of post traumatic distress disorder. Previous studies have demonstrated alterations in the salience network (SN) in patients with post traumatic distress disorder and that hyperactivity of the SN is associated with AVHs in patients with psychosis. Patients with post traumatic distress disorder may benefit from aripiprazole; however, studies investigating the effect of aripiprazole on AVHs and activity in the SN in patients with post traumatic distress disorder are scarce. Therefore, we conducted an outcomes analysis using functional magnetic resonance imaging to explore the effects of add-on aripiprazole treatment on AVHs and brain functional connectivity in patients with post traumatic distress disorder. AVHs were alleviated by add-on aripiprazole treatment (Auditory Hallucination Rating Scale [AHRS] score reduced by ≥ 50%) in 22.7% of patients. Functional activity in the SN was obviously decreased in patients in whom AHRS scores were reduced ≥ 50% following add-on aripiprazole treatment compared to patients in whom AHRS scores were reduced by <50%. The decrease in functional connectivity within the SN was significantly correlated with the reduction in total AHRS scores. Although this study was associated with several limitations, the findings suggest that add-on aripiprazole treatment can alleviate AVHs in patients with post traumatic distress disorder by reducing activity in the SN.